Adapting roughages varying in quality and curing processes to the Nutrition of Beef Cattle: Urea vs. Soybean meal in wintering and finishing rations for beef steers - Richardson, D.; Smith, E.F.; Brent, B.E. (Kansas Agricultural Experiment Station, 2011)
It is generally recognized that a readily available source of energy (preferable grain) must be in the ration of ruminants for efficient synthesis of protein from nonprotein nitrogen. Therefore, nonprotein nitrogen has been used primarily in finishing (high grain) rations. Although urea is used rather extensively, there is practically no information on the minimum amount of readily available energy (grain) needed for efficient utilization. This test was designed to compare soybean meal (natural protein) and urea (nonprotein nitrogen) on an equivalent nitrogen basis in wintering and finishing rations of beef steers calves. During the wintering phase, they were fed sorghum silage (made from sorghum that produced 85 bu. Grain per acre), 2lbs of average quality alfalfa hay, supplement and 0, 3 or 6 lbs. of added grain. In the finishing phase, 2 pounds prairie hay per head daily replaced the sorghum silage. The alfalfa hay was continued and all animals received a full feed of sorghum grain.
Keywords: Beef; Roughages; Urea; Soybean meal; Wintering ration; Finishing rations